Dyslipidemia associated with subclinical hypothyroidism in Eastern Nepal - Yadav, Rajaram; Rohil, Vishwajeet; Nepal, Ashwini Kumar; Gelal, Basanta; Chaudhari, Rajendra Kumar; Jha, Punam; Shrestha, Shreejana; Lamsal, Madhab; Baral, Nirmal (Asian Journal of Medical Sciences, 2014)
Objectives: The present study was conducted aiming to investigate lipid profile in patients with subclinical hypothyroidism as compared to age and sex matched controls. Methods: The study population consisted of total 80 subjects; 40 patients (cases) and 40 controls. Serum free tri-iodothyronine (fT3) and free thyroxine (fT4) were estimated by microplate competitive enzyme immunoassay, and thyroid stimulating hormone (TSH) measured by sandwich enzyme immunoassay. Lipid profile tests: Total Cholesterol, triglycerides, high density lipoprotein (HDL) cholesterol were estimated by enzymatic methods and low density lipoprotein cholesterol (LDL) was calculated by Friedewald’s formula. Results: Significant differences were observed between lipid parameters in case Vs controls: total cholesterol (4.9±1.1 Vs 4.3±1.0 mmol/L, P=0.03), triglycerides (1.9±0.7 Vs 1.6±0.6 mmol/L, P=0.02) and LDL cholesterol levels (3.5±1.1 Vs 2.9±0.9 mmol/L, P=0.02). In case Vs controls no significant differences were observed between HDL Cholesterol (1.1±0.2 Vs 1.1±0.7 mmol/L, P=0.07), VLDL (0.9±0.4 Vs 0.8±0.3 mmol/L, P=0.1) and Cholesterol/HDL ratio (4.48±1.40 Vs 4.06±0.89, P=0.118). Elevated TSH level were found in cases Vs controls (12.42±7.08 Vs 2.69±0.20 mIU/L, P=0.01) which was statistically significant. The subjects on control group were euthyroid, however increased fT3 (3.9±0.8Vs 4.6±0.8 pmol/L, P=<0.01) and fT4 (17.1±3.9Vs 21.2±.3.7 pmol/L, P=<0.01) values were observed in controls than cases, which was statistically significant. Conclusion: The results of the present study suggest that cases of subclinical hypothyroidism are at risk of dyslipidemia as compared to controls. Large population based studies are needed to generalize these findings and establish the therapeutic guidelines for implementing lipid lowering agents in subclinical hypothyroidism. Asian Journal of Medical Science, Volume-5(3) 2014: 22-25 http://dx.doi.org/10.3126/ajms.v5i3.9251